A Multi-Objective Simulation-Optimization framework for water resources management in canal-well conjunctive irrigation area based on nexus perspective - Hou, Jianzhe; Jiang, Yanan; Wei, Tingting; Wang, Zijun; Wang, Xiaojun (Journal of hydrology (Amsterdam), 2025)
•A framework for agricultural water-food-energy-ecosystem nexus management was developed.•Groundwater model with distributed planting structure was constructed.•The feasibility of the framework was demonstrated in Baojixia Irrigation Area.•Tradeoffs among nexus sectors based on different irrigation strategies were evaluated. Water scarcity drives the nexus of water-food-energy-ecosystem (WFEE) in arid and semi-arid agricultural irrigation areas, while the impacts of different irrigation strategies can propagate from water sector to other sectors through groundwater system. In this work, a Multi-Objective Simulation Optimization (MOSO) framework that couples the numerical groundwater model (MODFLOW) with the multi-objective optimization model (NSGA-III) is proposed to coordinate multiple resource systems with conflicting interests based on nexus perspective by reasonably allocating irrigation water resources from surface water diversion and groundwater abstraction. The management objectives include maximization of water use efficiency and food economic efficiency, as well as minimization of energy consumption efficiency and the impact of irrigation on ecosystem subject to groundwater levels, surface water supply and irrigation water demand. To demonstrate the feasibility of the MOSO framework, a water resources management problem in typical canal-well irrigation area − Baojixia Irrigation Area (BIA), located in Shaanxi province in northwest China, has been solved. The major findings are: (a) for every 10 % increase in the proportion of groundwater usage across the total irrigation area, water use efficiency decreases by 0.05 kg/m3, energy consumption efficiency increases by 900 CNY/ha, the ecosystem impact index decreases by 0.1, and food economic efficiency remains unchanged; (b) the four-dimensional Pareto-optimal solutions comprehensively consider all the impacts of the WFEE nexus system, avoiding decision shortsightedness caused by a low-dimensional perspective; (c) spatial differences in irrigation strategies across different zones are primarily influenced by crop structure, hydrogeological parameters and surface elevation, while temporal variations are mainly concentrated during the maize irrigation period. The framework based on water resources management and groundwater dynamics can efficiently evaluate trade-offs and synergies among nexus sectors, providing far-sighted suggestions for policy makers to improve resource-use efficiency, while mitigating the impact of irrigation on ecosystem.